Catechol-O-methyl transferase and schizophrenia - Šagud; Marina; Mück-Seler, Dorotea; Mihaljević-Peleš, Alma; Vuksan-Čusa, Bjanka Jakovljević, Miro; Pivac, Nela (2010)
The COMT Val108/158Met polymorphism is an almost irresistible target for genetic investigations, and combined worldwide, many thousands of cases and controls have now been studied, yielding positive and negative results. Heterogeniety of patient population has undoubtedly contributed to these inconsistent results. While the high activity Val allele is weakly, if at all, associated with the increased risk for schizophrenia, its interaction with other candidate genes, environmental factors, such as smoking, antipsychotic efficacy and adverse events, as well as its role in cognitive (dys)function is an exciting area for the future research.
Projekt MZOS
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG